Difficulties in chemical processing of dairy products in areas high andean peruvian - Vilca A., Miriam (2016)
This article seeks to highlight the difficulties in the chemical processing of dairy products in the experience of a project “Capacity Building for Improving the Competitiveness of Market Chains Dairy in Huaytará Province”, Department of Huancavelica. Which she worked with the communities of the highlands which had craft supplies, lacking proper techniques and with proper oversight in terms of hygiene in the treatment of milk which was strengthened and raised awareness through and provides them with training and training and technical assistance from a multidisciplinary at various annexes Cordova District team. It is suggested that more often this kind of scope of knowledge is carried out by qualified professionals who make a fundamental task for the sake of improving the quality of life of these communities, since the raw material is milk you get a countless products as described in this paper.